3D Nanofabrication of High‐Resolution Multilayer Fresnel Zone Plates. Issue 9 (5th June 2018) - Sanli, Umut Tunca; Jiao, Chengge; Baluktsian, Margarita; Grévent, Corinne; Hahn, Kersten; Wang, Yi; Srot, Vesna; Richter, Gunther; Bykova, Iuliia; Weigand, Markus; Schütz, Gisela; Keskinbora, Kahraman
Abstract: Focusing X‐rays to single nanometer dimensions is impeded by the lack of high‐quality, high‐resolution optics. Challenges in fabricating high aspect ratio 3D nanostructures limit the quality and the resolution. Multilayer zone plates target this challenge by offering virtually unlimited and freely selectable aspect ratios. Here, a full‐ceramic zone plate is fabricated via atomic layer deposition of multilayers over optical quality glass fibers and subsequent focused ion beam slicing. The quality of the multilayers is confirmed up to an aspect ratio of 500 with zones as thin as 25 nm. Focusing performance of the fabricated zone plate is tested toward the high‐energy limit of a soft X‐ray scanning transmission microscope, achieving a 15 nm half‐pitch cut‐off resolution. Sources of adverse influences are identified, and effective routes for improving the zone plate performance are elaborated, paving a clear path toward using multilayer zone plates in high‐energy X‐ray microscopy. Finally, a new fabrication concept is introduced for making zone plates with precisely tilted zones, targeting even higher resolutions. Abstract : Multilayer Fresnel zone plates (ML‐FZP) are fabricated using atomic layer deposition of amorphous‐oxide superstructures and focused ion beam slicing. ML‐FZPs are used as the lens in a soft X‐ray microscope and resolved 15 nm structures. A path forward is demonstrated by depositing on patterned micropillar arrays with tailored tapering angles for improving the efficiency and resolution beyond current state‐of‐the‐art values.